KELAYAKAN MEDIA FLASH CARDPADA SUBMATERI MANFAAT KEANEKARAGAMAN HAYATI DIKELAS X SMA KABUPATEN BENGKAYANG - Suripiana, Suripiana; Syamswisna, Syamswisna; Yokhebed, Yokhebed (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aimed to determine the feasibility of media flash cards. Medicinal plants used by the Dayak community of Bakati as specially in Sebente Village, Teriak Sub-district, Bengkayang Regency and to up flash cards of learning media as an implementation of ethnobotany research. The feasibility of flash cards on evaluated as learning media in the submaterial of biodiversity in Senior High School Class X. The method used in this qualitative research was descriptive method by using purposive sampling technique sampling. Then the result information of this research was implemented as flash cards media. It was evaluated by two lecturers of Biology Education Program, FKIP, Tanjungpura University and three Biology teachers of Senior High School class X in their schools in the Bengkayang Regency. Based on validation test, flash cards was categorized valid with the score average was CVI 0,99 and it was suitable as learning media in submaterial of biodiversity. Keywords: Biodiversity, Media, Flash Cards, Feasibility